In Situ Forming Bioartificial Hydrogels with ROS Scavenging Capability Induced by Gallic Acid Release with Potential in Chronic Skin Wound Treatment - Rossella Laurano; Alessandro Torchio; Gianluca Ciardelli; Monica Boffito (Gels, 2023)
In normal chronic wound healing pathways, the presence of strong and persistent inflammation states characterized by high Reactive Oxygen Species (ROS) concentrations is one of the major concerns hindering tissue regeneration. The administration of different ROS scavengers has been investigated over the years, but their effectiveness has been strongly limited by their short half-life caused by chronic wound environmental conditions. This work aimed at overcoming this criticism by formulating bioartificial hydrogels able to preserve the functionalities of the encapsulated scavenger (i.e., gallic acid—GA) and expand its therapeutic window. To this purpose, an amphiphilic poly(ether urethane) exposing -NH groups (4.5 × 1020 units/gpolymer) was first synthesized and blended with a low molecular weight hyaluronic acid. The role exerted by the solvent on system gelation mechanism and swelling capability was first studied, evidencing superior thermo-responsiveness for formulations prepared in saline solution compared to double demineralized water (ddH2O). Nevertheless, drug-loaded hydrogels were prepared in ddH2O as the best compromise to preserve GA from degradation while retaining gelation potential. GA was released with a controlled and sustained profile up to 48 h and retained its scavenger capability against hydroxyl, superoxide and 1′-diphenyl-2-picrylhydrazyl radicals at each tested time point. Moreover, the same GA amounts were able to significantly reduce intracellular ROS concentration upon oxidative stress induction. Lastly, the system was highly cytocompatible according to ISO regulation and GA-enriched extracts did not induce NIH-3T3 morphology changes.